PENERAPAN HEALING ARCHITECTURE PADA MASA PRE - POST PARTUM - Victoria Virginia; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Birth is the most anticipated moment for a mother and her family. The numerous adjustments a mother goes through during pregnancy and even after childbirth can lead to anxiety and stress, which may result in psychological disorders such as baby blues and postpartum depression. The approach of healing architecture in maternity accommodations, both during the prepartum (before birth) and postpartum (after birth) periods, can have an impact on the psychological well-being of the mother and her family. How can the aspects of healing architecture be implemented in building design and programs designed to meet the needs of the mother and contribute to indirect recovery by providing a comfortable environment? Incorporating elements of nature in the building design creates a natural impression and contributes to the healing process for mothers during these crucial periods. Various activity programs will be provided in the maternity accommodations for mothers during the pre- and postpartum periods to maintain their physical and mental well-being through enjoyable activities. These activities include yoga, spa treatments, and workshops that enhance the mother's physical readiness for childbirth and postpartum recovery, as well as activities that promote mental well-being, such as therapy and hypnobirthing classes to prepare the mother mentally. Keywords: healing architecture; prepartum; postpartum Abstrak   Kelahiran adalah momen yang paling ditunggu bagi seorang ibu dan keluarga. Banyaknya proses penyesuaian ibu saat kehamilan bahkan sesudah kelahiran menimbulkan kecemasan hingga stress yang dapat berakhir pada gangguan psikologis seperti baby blues dan postpartum depression. Pendekatan healing architecture pada fasilitas penginapan ibu yang sedang berada di masa prepartum (sebelum kelahiran) dan postpartum (setelah kelahiran) dapat berpengaruh terhadap psikologis ibu dan keluarga. Bagaimana aspek - aspek healing architecture dapat diterapkan pada desain bangunan dan program yang dirancang untuk memenuhi kebutuhan ibu dapat menjadi pemulihan secara tidak lansung karena ibu berada pada lingkungan yang nyaman. Pendekatan alam pada elemen - elemen bangunan menimbulkan kesan natural dan menjadi healing bagi ibu yang berada pada masa - masa krusial. Pada penginapan untuk ibu pada masa pre - post partum akan disediakan berbagai program aktivitas yang dapat menjaga kondisi ibu pada masa tersebut baik secara fisik dan mental karena program yang menyenangkan. Diantaranya adalah aktivitas yoga, spa, dan aktivitas workshop yang dapat meningkatkan kesiapan fisik ibu dalam menghadapi kelahiran maupun pemulihan fisik pasca melahirkan hingga aktivitas bagi mental ibu seperti terapi dan kelas hypnobirthing yang menyiapkan ibu secara mental.